2015
DOI: 10.1155/2015/408205
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance in Escherichia coli Strains Isolated from Infections in Dogs and Cats in Poland (2007–2013)

Abstract: The antimicrobial susceptibility of Escherichia coli isolates associated with various types of infections in dogs and cats was determined. The studied isolates were most frequently susceptible to fluoroquinolones and the extended-spectrum cephalosporins (ESCs), antimicrobials commonly used in treatment of infections in companion animals. However, an increase in the percentage of strains resistant to β-lactam antibiotics including ESCs was noted between January 2007 and December 2013. The frequency of multidrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 33 publications
8
49
5
3
Order By: Relevance
“…Isolation of diarrhoeagenic antimicrobial-resistant E. coli from dogs with or without diarrhoea and/or their handlers have been reported in countries such as Italy (Carattoli et al 2005), Portugal (Costa et al 2008, Bien et al 2011, Poland (Rzewuska et al 2015), Brazil (de Almeida et al 2012, Paula and Marin 2008, Paula and Marin 2009, Siqueira et al 2009, Puno-Sarmiento et al 2013, the Netherlands (Ewers et al 2010, Ewers et al 2012, Argentina (Bentancor et al 2007), America (Shaheen et al 2011), and Egypt (Ali andMetwaly 2015, Yunis et al 2015). In the available literature, studies on pathogenic E. coli in diarrhoeic and/or healthy dogs in Iran include the reports of Zahrei Salehi et al (2011) and Koochakzadeh et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of diarrhoeagenic antimicrobial-resistant E. coli from dogs with or without diarrhoea and/or their handlers have been reported in countries such as Italy (Carattoli et al 2005), Portugal (Costa et al 2008, Bien et al 2011, Poland (Rzewuska et al 2015), Brazil (de Almeida et al 2012, Paula and Marin 2008, Paula and Marin 2009, Siqueira et al 2009, Puno-Sarmiento et al 2013, the Netherlands (Ewers et al 2010, Ewers et al 2012, Argentina (Bentancor et al 2007), America (Shaheen et al 2011), and Egypt (Ali andMetwaly 2015, Yunis et al 2015). In the available literature, studies on pathogenic E. coli in diarrhoeic and/or healthy dogs in Iran include the reports of Zahrei Salehi et al (2011) and Koochakzadeh et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to three or more classes of antibacterial agent implies multidrug resistance (Tenover 2006;Nam et al, 2010;Rzewuska et al, 2015). In this study, resistance of all the Salmonella isolates to three or more of the antibacterial agents suggested that isolates in the genus exhibited higher multidrug resistance when compared with the multidrug resistance of the E. coli (81.8%) and Klebsiella (70%) isolates.…”
Section: Referencesmentioning
confidence: 61%
“…It is also higher than 16, 7, 6.6 and 2.6% ESBL-resistant/producing E. coli isolation prevalence in 100 extra-clinical faecal samples of dogs in Germany (Schaufler et al, 2015), among 445 clinical E. coli isolates from companion animals in United Kingdom (UK) (Timofte et al, 2016), faecal samples of 75 healthy dogs/cats (Costa et al, 2004) and 39 healthy dogs (Costa et al, 2008) reported in Portugal, respectively. Pomba et al (2009), Tamang et al (2012, Rzewuska et al (2015), Caratolli et al (2005), O'Keefe et al (2010), Huber et al (2013) and Feira et al (2002) reported 1.6, 2.9, 28.2, 7, 5, 7.5 and 1.4% ESBLproducing/resistant E. coli isolation prevalence among 61, 730, 628, 298, 257, 107 and 72 E. coli isolates from urine/urinary tract of sick dogs in Portugal, dogs/cats in Poland, intestinal E. coli isolates from stray dogs in South Korea, sick/healthy dogs/cats/rat in Italy, urine/urinary tract of sick dogs/cats in America and Switzerland, and healthy dogs in Portugal, respectively. These results are also lower than 40.7% E. coli isolation prevalence recorded in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One concerning trend documented in recent years has been the increased prevalence of nonsusceptibility to antimicrobials observed in canine urinary tract isolates, in particular to fluoroquinolones, third generation cephalosporins, and clavulanic acid-potentiated β-lactams (Cooke et al, 2002;Mazzuli, 2002;Ball et al, 2008;Sidjabat et al, 2009;Platell et al, 2011a;Hall et al, 2013;Wagner et al, 2014;Chang et al, 2015;Rzewuska et al, 2015). The availability of many of these drugs in oral forms that reach high concentrations in the urine following absorption, along with their efficacy against Gram-negative pathogens in particular, has resulted in their widespread use in companion animals.…”
Section: Observations Of Increasing Antimicrobial Resistance In Caninmentioning
confidence: 99%